Exploring Ritual Fields Today (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Rituals, although seemingly traditional and fixed, a re v ery m uch contextualand subject to change. Rituals do not exist and are not performed in a vacuum,and are not independent of time and place. They are deeply influenced by thecultural, social, economic, and political contexts in which they appear. Trendsin culture also lead to ritual trends. Therefore, rituals are a dynamic field, whichis reflected in this Special Issue of Religions regarding "Exploring RitualFields Today".